Kekerasan Seksual Terhadap Perempuan: Realitas dan Hukum: Realitas dan Hukum - Siregar, Elizabeth; Rakhmawaty, Dessy; Siregar, Zulham Adamy (PROGRESIF: Jurnal Hukum, 2020)
Violence against women is a crime that almost occurs in all cultures and countries that occur both in public and private spaces. Based on Komnas Perempuan's annual records, almost all regions of Indonesia committed these crimes. The most common violence is sexual violence. In Jambi, during the period of 2017-2019 there were several cases of rape and sexual abuse and other violence. And what's interesting is that some cases have other dimensions of action that are actually important to study how the application of the law to the event. This research is empirical, because it examines facts or legal events by then examining how the application of the law. From the results of the study showed that, the type of sexual violence decided by the judge, generally related to the crime of rape and molestation as contained in the Criminal Code. In the imposition of sanctions, none of the judges has given the maximum sentence, even though the trial proved guilty. In the case of the application of the law, law enforcers in this case prosecutors and judges guide the Criminal Code, which indeed includes rape and molestation arrangements. Although in reality the actual cases have different dimensions of action (more than one) and deserve to be given threats that are in accordance with the perpetrators' actions. In this case, there is a legal vacuum that actually results in uncertainty in fulfilling a sense of justice for women (victims). So it is important to reform the provisions regarding sexual violence by adopting the value of protecting women and accommodating the wisdom principle of the Indonesian nation namely Pancasila and accommodating the principles of gender justice